If fx =x - 12x2 - 7x + 5,

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

1011.

If :R→ R  defined by

f x = a2cos2x + b2sin2x,   x  0         = eax + b,                    x >0is continuous function,  then

 

  • b = 2loga

  • 2b = loga

  • b = log2a

  • b2 = loga


1012.

Let f(x) = ex, g(x) = sin - 1x and h(x) = f(g(x)), then

h'xhx is equal to

  • sin-1x

  • 11 - x2

  • 11 - x

  • esin-1x


1013.

If  fx = ax + a2ax, then f'a is equal to

  • 0

  • - 1

  • 1

  • a


1014.

If y = aex + be-x + c, where a, b, c are parameters, then x2y" + xy' is equal to 

  • 0

  • y

  • y'

  • y''


Advertisement
1015.

If y = acos(log (x)) + bsin (log(x)), where a, b are parameters, then xy" + xy' is equal to

  • y

  • - y

  • 2y

  • - 2y


1016.

The two curves x = y2, xy = a2 cut orthogonally at a point, then a2 is equal to

  • 13

  • 12

  • 1

  • 2


1017.

If f(x) = 1 + kx - 1 - kxx, for - 1  x< 02x2 + 3x + 2,               for 0  x  1is continuous at x = 0, then k is equal to

  • - 1

  • - 2

  • - 3

  • - 4


Advertisement

1018.

If fx =x - 12x2 - 7x + 5, for x  1                 - 13, for x = 1, then f'1 is equal to :

  • - 19

  • - 29

  • - 13

  • 13


B.

- 29

We have,f(x) = x - 12x2 - 7x + 5, x  1       = x - 12x2 - 2x - 5x + 5       = x - 12xx - 1 - 5x - 1 = 12x - 5f(x) = 12x - 5, x  1- 13,      x = 1Now,  f'(x) = limh0 f1 + h -f1h                 = limh0 121 + h - 5 - - 13h                 = limh0 12h - 3 + 13h                = limh0 3 + 2h - 332h - 3                =limh0 232h - 3 = - 29


Advertisement
Advertisement
1019.

If fx = x1 + x, for x  R, then f'0 is equal to :

  • 0

  • 1

  • 2

  • 3


1020.

If u(x, y) = ylog(x) + xlog(y), then

uxuy - uxlog(x) - uylog(y) + log(x)log(y) is equal to

  • 0

  • - 1

  • 1

  • 2


Advertisement